Grid-connected Integrated Community Energy System. Preliminary report, Phase II, August 9--November 8, 1977. [Clark Univ. , Worcester] (Clark University (Worcester, Mass.), 1977)
Clark University in the New England area represents an attractive site for demonstration of cogeneration. In Phase I of the program, the team reported: that the system of choice is a diesel generator sized at about Clark's peak electric demand; it should burn No. 6 fuel oil; the system can run at nearly full capacity the year round, sell 40 percent of its output, and receive backup as needed from Massachusetts Electric Company; the system should deliver a rate of return of 15 to 20 percent; and there appear to be no institutional or environmental problems. An update on a number of issues that were incompletely resolved in the Phase I report is provided. In Section 2 additional documentation on institutional issues involved in the proposed demonstration plant is provided. In Section 3 a preliminary design analysis that clearly defines the choice of engine and provides revised operating data in light of additional load profile studies is provided. In particular, it is found that: a Sulzer No. 6-oil-burning 1405-kW diesel is the system of choice; the engine should be housed in a separate building in close proximity to the existing central boiler and steam distribution points; and as a result of detailed summer load studies, the engine as specified can be operated with higher capacity factors than anticipated in Phase I. In Section 4 a revised cost estimate using information developed in Sections 2 and 3 is given. No significant change in net cash flow was found, and there was an internal rate of return of 15 percent. The overall conclusion is therefore that, though some details have changed, the Clark demonstration project continues to appear highly attractive. (MCW)